Investigating psychological well-being and resilience among international college students in the United States - Chaliawala, Kruti S.; Vidourek, Rebecca V.; King, Keith A.; Merianos, Ashley L. (Journal of International Students, 2025)
This study examines psychological well-being and resilience, focusing on how demographic characteristics and stress levels impact mental health among international students. A secondary data analysis was conducted via the National College Health Assessment (2022). Approximately 82.7% of the participants reported moderate to high levels of psychological well-being. High resilience was linked to increased well-being (AOR = 7.03, p < .001), whereas high stress (AOR = 0.40, p < .001) and being female (AOR = 0.70, p < .001) were associated with lower well-being. The results highlight the role of resilience in reducing acculturative stress and enhancing overall well-being. Tailored policies and culturally sensitive support are necessary for the well-being of international